Clinicopathologic features and genetic characteristics of the BRCA1/2 mutation in Turkish breast cancer patients - Cecener, Gulsah; Sabour Takanlou, Leila; Sabour Takanlou, Maryam; Egeli, Unal; Eskiler, Gamze Guney; Aksoy, Secil; Unal, Ufuk; Tezcan, Havva; Eryilmaz, Isil Ezgi; Gokgoz, Mustafa Sehsuvar; Tunca, Berrin; Cubukcu, Erdem; et al. (Cancer genetics, 2020)
•The BRCA1/2 mutations were evaluated with clinicopathological features and genetic characteristics in 603 Turkish breast cancer patients.•The c.5266dupC mutation is one of the most frequently reported mutations in BRCA1 and the most common BRCA2 gene mutations in the present study were c.8940delA and c.9097dupA.•The variants based on classification categories identified in our cohort, 14 variants seem to be unique to the Turkish population.•Additionally, among the cases screened for BRCA1/2, 7 variants were detected with uncertain significance.•These results could contribute to management of the breast cancer patients. The aim of this study was to identify the frequency and spectrum of germline BRCA1/2 pathogenic alterations in a cohort of patients with breast carcinoma. In this study, a total of 603 breast cancer subjects from Turkey were screened for BRCA1/BRCA2 mutations using HDA and Sanger sequencing. In the present study, 21 BRCA1 and BRCA2 pathogenic variants were detected in 30 patients and BRCA1/2 mutations were significantly associated with a family history of breast/ovarian cancer. Analysis of overall survival for BRCA1/BRCA2 mutation carriers showed a trend for poor overall survival only in BRCA1 carriers, although this was not statistically significant in BRCA1 and BRCA2 mutation carriers. The c.5266dupC mutation is one of the most frequently reported mutations in BRCA1 and was identified in five breast cancer patients in our study. The most common BRCA2 gene mutations in the present study were c.8940delA and c.9097dupA, which were found in seven patients. We found mostly BRCA1 and BRCA2 mutation carriers in those patients who showed hormone-positive features. In conclusion, our data showed differences in the distribution of the mutation spectrum of BRCA1 and BRCA2 in Turkey.